Bioaccumulation and risk assessment of radiocesium in the Northwest Pacific Ocean from Fukushima Dai-ichi Nuclear Power Plant accident - Abbasi, Akbar (Pergamon-Elsevier Science Ltd, 2023)
To understand which biota are more exposed to radionuclides, the bioaccumulation and risk assessment of radiocesium (137Cs and 134Cs) release from FDNPP in the Northwest Pacific Ocean were analyzed using ERICA tools. The activity level was determined by the Japanese Nuclear Regulatory Authority (RNA) in 2013. The data were used as input to the ERICA Tool modeling software to evaluate the accumulation and dose of marine or-ganisms. The highest and lowest accumulate concentration rate were observed in birds (4.78E+02 Bq kg- 1/Bq L-1) and the Vascular plant (1.04E+01 Bq kg-1/Bq L-1), respectively. The total dose rate range for the 137Cs and 134Cs ranged between 7.39E-04 and 2.65E+00 mu Gy h-1 and 4.24E-05 and 2.91E-01 mu Gy h-1, respectively. There is no considerable risk to the marine biota in the research region since the cumulative dose rates of radiocesium to the chosen species were all less than 10 mu Gy h-1.
Keywords: Risk assessment; Bioaccumulation; Fukushima; ERICA Tool; 137Cs; 134Cs